EFFECTIVENESS OF A DIGITAL SCHOOL PROGRAM IN STRENGTHENING STUDENTS’ CHARACTER AND COMPETENCE: A CASE STUDY AT MUHAMMADIYAH 5 RANDUBLATUNG JUNIOR HIGH SCHOOL - Siti Naviah Nurhayati; Widya Kusumaningsih; Joko Sulianto (SOSIOEDUKASI, 2026)
The rapid advancement of digital technology has encouraged schools to adopt innovative programs aimed not only at improving academic achievement but also at fostering students’ character and competencies. This study investigates the effectiveness of a Special Digital Program implemented at Muhammadiyah 5 Randublatung Junior High School in strengthening students’ character and twenty-first-century competencies. A qualitative case study approach was employed to obtain an in-depth understanding of program outcomes within its natural context. Data were collected through classroom observations, semi-structured interviews with school leaders and teachers, and analysis of institutional documents. The findings reveal that the program effectively promotes positive character traits, including discipline, responsibility, ethical awareness, and collaborative attitudes, particularly in digital learning environments. In addition, students demonstrate significant improvement in competencies such as digital literacy, critical thinking, creativity, communication, and problem-solving skills. The program’s effectiveness is supported by strong leadership commitment, teachers’ readiness to integrate technology into instruction, and an adaptive school culture. Overall, the program functions as an integrative educational strategy that simultaneously develops moral values and essential competencies, highlighting the potential of school-based digital initiatives to support holistic student development.